In order to find out what 36x + 9 is equivalent to,, we must factor out 9 from the expression. Once we do this you will find that this expression is equivalent to 9(4x + 1),, or option E.
Next we will look at the expression 9(4x -1). In order for us to find out the equivalent to this expression,, we must first multiply each term in the parenthesis by 9.
9 × 4x - 9
Now calculate the product
36x - 9
This means that the equivalent for this expression is 36x - 9,, or option A.
Lastly,, we will look at the final expression given which is 4(9x + 2). The first step for finding the equivalent of this expression is to multiply the numbers in the first parenthesis together.
(36x) + (4 × 2)
Now multiply the numbers in the second parenthesis together.
(36x) + 8
Remove the parenthesis
36x + 8
Now factor out 4 from the expression to get your final answer.
4(9x + 2)
This means that the last expression is equivalent to 4(9x + 2),, or option C.
Let me know if you have any further questions
:)
3.2n=3.2*5
3.2*5=16 the answer is 16
Hope this helps, have a great day!!
:)
Answer:
a=2
b=3
c=5
d=-3
Step-by-step explanation:
a + b = c
a-c=d
a+b=5
a+b =5
a = 2
2+b =5
Subtract 2 from each side
2+b-2 =5-2
b=3
a + b = c
2+3 = c
5=c
a-c=d
2-5 =d
-3 =d
Hello from MrBillDoesMath!
Answer:
Increasing on the interval [-5, -2]
Discussion:
The function value remains unchanged on [-2, 1] and decreases on [1,8]
Thank you,
MrB